Generic Fragmentation in Modern Campaign Rhetoric: A Study of the 2020 U.S. Presidential Announcements. (January 2022) - Neville-Shepard, Ryan
This essay suggests that campaign speech genres have transformed in the digital era due to what I call "generic fragmentation." Speeches that are expected of political candidates have been replaced by discourse that is scattered over a variety of channels, while taking a form that is truncated, fragmented, and unlikely to satisfy generic conventions when analyzed individually. Illustrating this argument, this essay focuses on the campaign announcements from the 2020 U.S. presidential election to show how the classic announcement speech has transformed into the "long announcement, " spread out over a longer period of time and often in scattered fragments, thus challenging the ways such messages can be evaluated by political communication critics.